From Modernisation to Big Society: Continuity and Change in Social Work in the United Kingdom - Ferguson, Iain (Cuadernos de Trabajo Social, 2012)
In this paper, I will explore developments in social work in the United Kingdom since the formation of the Conservative/ Liberal Democrat Coalition Government in May 2010. I will argue that the period since then has been characterised by elements both of continuity and change: continuity in that the neoliberal assumptions which underpinned New Labour’s approach to social work continue to inform the approach of the Coalition; change, in that there is evidence of a more vigorous anti-statist rhetoric, reflected both in a critique of “bureaucracy” and also in the promotion of the Big Society as an all-embracing ideological framework. Against those who see the Big Society project as providing an opportunity for the emergence of a more progressive social work, I will argue that its primary rationale is to shift responsibility from the welfare state onto individuals and communities. The final part of the paper will explore some of the implications of the Big Society approach for social work and social care, through consideration of the policies of personalisation, localism and “open public services”.